On the relationship between quantity and quality of a country's research productivity - Lawani, S.M. (1982)
Analyses of a sample of cancer research papers previously judged to be of high quality and of a random sample from the world literature, indicate that nineteen countries are the key producers of cancer research literature. Quality papers were much less dispersed among countries than ordinary papers and there was a high and statistically significant correlation be tween the quantity and the quality of productivity of countries.